The impact of “Panama Leaks” on the Stock Market: Empirical Evidence from the Emerging Equity Market - Muhammad Husnain; Syeda Nitashah Anwer; Shahjahan Sarfraz Raja (NUML International Journal of Business & Management)
The aim of the present study is to examine the effect of the events related to the “Panama leaks” on the stock market in Pakistan. For this purpose, we have analyzed a total of 24 events related to the “Panama leaks” in Pakistan. These events are further divided into three broad categories i.e. 8 events are related to the news/statements by the opposition parties, 8 events are related to news/statements by Sharif’s family/sitting governments, and 8 events are related to the news/statements by the Apex court in Pakistan. The analyzed period begins on the 1st of March 2015 and has lasted until the 30th of July 2018. This research applies the event study methodology, and overall findings show that “Panama leaks-related news has a significant impact on stock returns in Pakistan. What is more, all the news related to the Apex court in the Panama leaks show a significant positive impact on stock returns. This study provides a guideline to investors, regulators, policymakers, and other stakeholders by proving that all the news related to the “Panama leaks” have a significant impact on stock returns in Pakistan. Future researchers can extend this study by analyzing the impact of the “Panama leaks” on stock returns in all the countries to which the “Panama leaks” are connected.